2014
DOI: 10.1378/chest.14-0126
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Exacerbations in Indigenous Children From Two Countries With Non-Cystic Fibrosis Chronic Suppurative Lung Disease/Bronchiectasis

Abstract: BACKGROUND:Acute respiratory exacerbations (AREs) cause morbidity and lung function decline in children with chronic suppurative lung disease (CSLD) and bronchiectasis. In a prospective longitudinal cohort study, we determined the patterns of AREs and factors related to increased risks for AREs in children with CSLD/bronchiectasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 27 publications
3
34
0
1
Order By: Relevance
“…Nevertheless, chronic cough is a common problem in populations in LMICs in which HAP exposures are high and the underlying causative factors and pathology of chronic cough in these settings have not been characterised because CT scanning and epidemiological studies are not available. Bronchiectasis, or a syndrome that could perhaps more pragmatically be described as complex airways disease, which overlaps with other diagnoses such as chronic bronchitis, is a probable contributor to this burden of chronic cough, as has been shown in indigenous children in developed countries 168,169. This disorder is likely to be the result of many respiratory insults across the lifespan including in-utero and early life malnutrition, predisposition to and repeated episodes of acute lower respiratory tract infections, poor access to prompt effective treatment for ALRI, HIV infection, and complications after pulmonary tuberculosis.…”
Section: Obstructive Lung Diseasementioning
confidence: 99%
“…Nevertheless, chronic cough is a common problem in populations in LMICs in which HAP exposures are high and the underlying causative factors and pathology of chronic cough in these settings have not been characterised because CT scanning and epidemiological studies are not available. Bronchiectasis, or a syndrome that could perhaps more pragmatically be described as complex airways disease, which overlaps with other diagnoses such as chronic bronchitis, is a probable contributor to this burden of chronic cough, as has been shown in indigenous children in developed countries 168,169. This disorder is likely to be the result of many respiratory insults across the lifespan including in-utero and early life malnutrition, predisposition to and repeated episodes of acute lower respiratory tract infections, poor access to prompt effective treatment for ALRI, HIV infection, and complications after pulmonary tuberculosis.…”
Section: Obstructive Lung Diseasementioning
confidence: 99%
“…The principles of management for non-CF bronchiectasis are regular sputum clearance exercises and early, aggressive treatment of exacerbations, 7 in addition to investigation for an underlying cause at diagnosis. 10,11 Guidelines recommend that these exacerbations are treated with a 10-to 14-day course of antibiotics and, when required, hospital admission of ≥7 days for intensive therapy. 9 Infective exacerbations of bronchiectasis cause significant morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…A study of 93 Indigenous children from Alaska and Australia with CSLD or bronchiectasis (42) reported 74% of children experienced >2 exacerbations over a 3-year period. In this study, the factors associated with recurrent episodes were young age (<3 years), hospitalization for an acute exacerbation in the first-year of life, and pneumonia or hospitalization for an acute exacerbation in the year preceding enrollment (42).…”
Section: Etiologymentioning
confidence: 99%
“…A study of 93 Indigenous children from Alaska and Australia with CSLD or bronchiectasis (42) reported 74% of children experienced >2 exacerbations over a 3-year period. In this study, the factors associated with recurrent episodes were young age (<3 years), hospitalization for an acute exacerbation in the first-year of life, and pneumonia or hospitalization for an acute exacerbation in the year preceding enrollment (42). Exacerbations are also more frequent in severe bronchiectasis, and one study of 111 children reported that intensive medical intervention reduced the annual exacerbation rate by 56%; however, children still experienced a mean of 2.9 episodes per year (43).…”
Section: Etiologymentioning
confidence: 99%